Tinjauan Offensive Realism: Keluarnya Amerika Serikat dari Paris Agreement di Tahun 2017 - Kusuma Sari, Luh Putu Ariska; Sushanti, Sukma; Kumala Dewi, Putu Ratih (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2019), 2019)
ABSTRACT This research aims to explain the background of the United States who decided to leave the Paris Agreement in 2017, by using a qualitative research method. The United States is one of the countries that joined the UNFCCC. As a developed country that produces the second highest carbon emissions in the world, the United States is certainly expected to commit to a climate change agreement, to reduce its country's carbon emissions. In 2016, the United States joined the climate change institution called Paris Agreement. But unfortunately, one year later the United States decided to leave the institution. The framework that the Researcher use consist of the theory of Offensive Realism and the concept of Institution according to the realist perspective. Through this research, it is recognized that Paris Agreement was not in accordance with The United States’s national objective in achieving hegemony in the coal production. Keywords : United States, Paris Agreement, Offensive Realism, Institutions According to Realists